IDENTIFIKASI KANDUNGAN UNSUR HARA PADA LAHAN TAMBANG DESA TALAWAAN - Mutiara Putri Amalia; Wiesje J. N. Kumolontang; Zetly E, Tamod (Universitas Sam Ratulangi, 2021)
ABSTRACTNutrients of nutrients are important factors for plant growth which can belikened to food substances for plants. Plant nutrient contents of N, P, and K in themining area of Talawaan Village was studied in this research. Soil samples from threedifferent places at the mining site were taken and analyzed at the Laboratory ofChemistry and Soil Fertility. Analysis of plant available Nitrogen utilized Kjedhalmethod and plant available P and K used Bray 1 method, The findings show that theplant available nutrient of N, P and K is classified from low to very low, while soil pHof the Talawaan Village Mining area is neutral. It is suggested to increase the nutrientavailability for plants in this location by adding organic fertilizers.Keywords: Plant available nutrients, Nitrogen, Phosphorus and Potassium